Treatment of Peroneal Nerve Injuries in the Multiligament Injured/Dislocated Knee - O'Malley, Michael P.; Pareek, Ayoosh; Reardon, Patrick; Krych, Aaron; Stuart, Michael J.; Levy, Bruce A. (The Journal of Knee Surgery, 2016)
Tibiofemoral knee dislocations are typically a consequence of high-energy mechanisms, causing significant damage to the soft tissue and osseous structures of the knee. Concomitant neurovascular injuries such as popliteal artery and peroneal nerve injuries are also common and can have significant long-term consequences. The mechanism typically involves a traction injury to the peroneal nerve subsequent to an extreme varus moment applied to the knee. Complete nerve injuries typically hold a worse prognosis than incomplete palsies. Rates of functional recovery in the setting of a complete palsy following a knee dislocation event have been dismal. A period of observation and nonoperative treatment is initially performed, utilizing orthotic devices to assist with lower extremity deficits. Surgical treatment options include neurolysis, nerve grafting, tendon transfer, arthrodesis, and direct motor nerve transfers. Motor nerve transfers continue to be explored with initial reports showing promising results.
Keywords: peroneal nerve; nerve repair; nerve grafting; knee dislocation